Characterizing T?cell receptor ??variable gene in Aotus nancymaae owl monkey peripheral blood (2003)
Gd T lymphocytes have a heterodimeric complex formed by theassociation of g and d chains as receptor. Proliferation of this lymphocytepopulation has been observed, when infection by several pathogens such asMycobacterium tuberculosis and Plasmodium spp. occurs. The New WorldMonkey Aotus nancymaae has become a very good experimental model forthe immunological and physiopathological study of these infectious agents.The A. nancymaae g-variable region was characterized from peripheral bloodsamples by using cDNA and genomic DNA polymerase chain reactionamplification, DNA sequencing, and dot-blot hybridization techniques.Seventeen different T-cell receptor g-variable (TCRGV) sequences wereobtained. These sequences were distributed among TCRGV subsets 1, 2, or 3,according to human subset classification. Although no subset 4 amplificationwas obtained, this subset was detected by dot-blot hybridization. Thepresence of these 4 subsets resembles the behavior displayed by ‘gd-lowspecies’ (humans and mice), where high diversity among these lymphocytescan be observed. Homologies greater than 70% were found with respect tohumans. Sequence convergence between human and A. nancymaae subsets1 and 3 highlights Aotus as a promising model for studying these lymphocytefunctions.